Lymphatic Drug Absorption via the Enterocytes: Pharmacokinetic Simulation, Modeling, and Considerations for Optimal Drug Development - Dion R. Brocks; Neal M Davies (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
Most orally administered drugs gain access to the systemic circulation by direct passage from the enterocyte layer of the intestinal tract to the mesenteric blood capillaries. Intestinal lymphatic absorption is another pathway that certain drugs may follow to gain access to the systemic circulation after oral administration. Once absorbed, drug diffuses into the intestinal enterocyte and while in transit may associate with fats as they are processed into chylomicrons within the cells. The chylomicron-associated drug is then secreted from the enterocyte into the lymphatic circulation, thus avoiding the hepatic first-pass liver metabolism, and ultimately entering to the systemic circulation for disposition and action. Due to the possibility of parallel and potentially alternative absorptive pathways, mesenteric blood capillary and lymphatic drug exposure are both potential pathways of systemic availability for any individual drug. In this report, an in silico modeling approach was adopted to delineate the salient pharmacokinetic features of lymphatic absorption, and provide further guidance for the rationale design of drugs and drug delivery systems for lymphatic drug transport. The importance of hepatic extraction ratio, absorption lag time, lipoprotein binding, and the influence of competing portal and lymphatic pathways for systemic drug availability were explored using simulations. The degree of hepatic extraction was found to be an essential consideration when examining the influence of lymphatic uptake to overall oral drug bioavailability. Lymphatic absorption could potentially contribute to multiple peaking phenomena and flip flop pharmacokinetics of orally administered drugs.